ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI KABUPATEN LOMBOK TENGAH TAHUN 2015-2022 - Japarussidik, Japarussidik; Sahar, Sahar; Suhendri, Ahmad (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2025)
Various forms of social assistance programs for poverty alleviation have been implemented by the government.Social assistance from the government is in the form of the Family Hope Program (PKH), Non-Cash FoodAssistance (BPNT), Prosperous Rice (Rastra), Village Funds, Healthy Indonesia Card (KIS) and SmartIndonesia Card (KIP). According to data from BPS, although the number of poor people in Central LombokRegency has decreased, in reality there is still a lot of poverty, such as low education problems, minimaleconomic problems, lack of employment opportunities, high inflation so that many people are still unemployedand many workers are still paid low wages, and uneven development problems. This study aims to determinewhat factors influence the poverty rate in Central Lombok Regency in 2015-2022. The research method used isquantitative with an associative approach. Data were analyzed using multiple linear regression methods. Theresults of the study showed that the level of education factor has an impact on the poverty rate. Thus, thepresence of the central and district governments is expected to provide policies on education for theunderprivileged.